(untitled) (Nigerian Journal of Pharmaceutical Research, 2025)
Background: The general use of herbal drugs is gaining wide popularity. Part of the quality attributes of a drug is its safety and efficacy, as these are important components of quality assurance in the production and use of drugs. The presence of heavy metals in herbal drugs can have severe health consequences. Therefore, there is need to evaluate the quality of plant materials used for therapeutic and drug development purposes. Objectives: The aim of this study is to determine the level of cadmium, lead, zinc, calcium, magnesium and nickel, and evaluate their health risk index in herbal plant, Erythrina senegalensis. Materials and Methods: The leaves of the plant were obtained from traditional medicine suppliers at the local market of Mushin, Lagos. The plant extract was digested using a mixture of hydrochloric acid and nitric acid in the ratio of 3:1. cadmium, lead, zinc, calcium, magnesium and nickel were determined using Atomic Absorption Spectrophotometer and health risk index was determined. Results: The results obtained showed that cadmium concentration (3.21 mg/kg) was above the permissive limit set by FAO/WHO. The health risk index (HRI) showed that cadmium (8504, 15765) and zinc (62.6617, 167.0977) values in adults and children were respectively greater than 1 which implies that users are considered to be at risk of various health complications that arise from the consumption of heavy metals beyond the required daily intake. Conclusion: This study highlights the concerning levels of cadmium and lead in the herbal plant, which pose potential health risks despite the presence of beneficial minerals like calcium and magnesium; and the presence of nickel and zinc at concentrations below the expected limits. The findings underscore the urgent need for stringent monitoring and regulation of heavy metal content in herbal products to ensure consumer safety.